2011
DOI: 10.1007/s10815-011-9677-7
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte morphology does not affect post-warming survival rate in an egg-cryobanking donation program

Abstract: Purpose To evaluate whether oocyte dysmorphisms affect oocyte survival rates in an egg-cryobanking donation program. Methods This study included 54 patients undergoing intracytoplasmic sperm injection. A total of 415 metaphase II oocytes were vitrified using the Cryotop method. Oocyte morphology was assessed immediately prior to oocyte vitrification under 400× magnification. The influence of dysmorphisms on post-thaw survival rates was assessed using regression analysis. Results were considered to be significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Cost‐efficiency of planned OC is contingent on the efficacy of the process alongside timing of planned OC, and the degree of utilisation of banked oocytes. There is limited literature exploring the efficacy of oocytes yielded from planned OC; four studies found the post thaw survival rate to hover around 85%; 26,62–64 however, there is much more variability in the data regarding fertilisation and clinical pregnancy rates. This variability, with a range of 66–84% for fertilisation rates and a range of 39–84% for clinical pregnancy rates, can be attributed in part to small sample sizes as well as to the heterogeneity of populations in the different studies 62,64–67 .…”
Section: Discussionmentioning
confidence: 99%
“…Cost‐efficiency of planned OC is contingent on the efficacy of the process alongside timing of planned OC, and the degree of utilisation of banked oocytes. There is limited literature exploring the efficacy of oocytes yielded from planned OC; four studies found the post thaw survival rate to hover around 85%; 26,62–64 however, there is much more variability in the data regarding fertilisation and clinical pregnancy rates. This variability, with a range of 66–84% for fertilisation rates and a range of 39–84% for clinical pregnancy rates, can be attributed in part to small sample sizes as well as to the heterogeneity of populations in the different studies 62,64–67 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that not only the morphological characteristics of the first PB, but also the angle of its location with respect to the pronuclei that appear after fertilisation, are important in predicting the quality of embryos. 43 Oocyte first-PB morphology observed prior to vitrification can predict post-warming survival, and developing non-invasive identification of predictive markers for oocyte survival potential remains relevant.…”
Section: Should All Aspirated Maturementioning
confidence: 99%